Novel molecular insights into the critical role of sulfatide in myelin maintenance/function - Palavicini, Juan Pablo (J Neurochem, 2016)
Cerebroside sulfotransferase (CST) catalyzes the production of sulfatide, a major class of myelin-specific lipids. CST knockout (CST(−/−)) mice in which sulfatide is completely depleted are born healthy, but display myelin abnormalities and progressive tremors starting at 4–6 weeks of age. Although these phenotypes suggest that sulfatide plays a critical role in myelin maintenance/function, the underlying mechanisms remain largely unknown. We analyzed the major CNS myelin proteins and the major lipids enriched in the myelin in a spatiotemporal manner. We found a one-third reduction of the major compact-myelin proteins (myelin basic protein, MBP, and proteolipid protein, PLP) and an equivalent post-developmental loss of myelin lipids, providing the molecular basis behind the thinner myelin sheaths. Our lipidomics data demonstrated that the observed global reduction of myelin lipid content was not due to an increase of lipid degradation but rather to the reduction of their synthesis by oligodendrocytes. We also showed that sulfatide depletion leads to region-specific effects on non-compact myelin, dramatically affecting the paranode (neurofascin 155) and the major inner-tongue myelin protein (myelin-associated glycoprotein). Moreover, we demonstrated that sulfatide promotes the interaction between adjacent PLP extracellular domains, evidenced by a progressive decline of high molecular weight PLP complexes in CST(−/−) mice, providing an explanation at a molecular level regarding the uncompacted myelin sheaths. Finally, we proposed that the dramatic losses of neurofascin 155 and PLP interactions are responsible for the progressive tremors and eventual ataxia. In summary, we unraveled novel molecular insights into the critical role of sulfatide in myelin maintenance/function.